Compatibility of peripapillary choroidal thickness measurement between 4-point manual measurement and measurement by manual re-segmentation in eyes with and without glaucoma (Annals of Medical Research, 2023)
Aim: To evaluate the compatibility of peripapillary choroidal thickness (PPCT) measurement using 4-point manual measurement and measurement by manual re-segmentation in glaucomatous and non-glaucomatous eyes.Materials and Methods: A total of 270 eyes of 135 consecutive patients were included in the study. Of these, 79 eyes had glaucoma. Optical coherence tomography (OCT) images of peripapillary circle scans were investigated with Heidelberg Spectralis OCT. PPCT at the 3.4 mm circular line around the disc was measured by 2 techniques; manual 4-point measurement (PPCT-1) at temporal, superior, nasal and inferior sectors and by changing retinal nerve fiber layer (RNFL) segmentation lines manually using the editing function and obtaining automatic calculations (PPCT-2). Compatibility of the 2 techniques and correlations with RNFL measurements, age, sex, glaucoma presence, glaucoma drug usage, glaucoma stage, mean deviation, spherical equivalent (SE) and corneal thickness were investigated.    Results: The mean PPCT measured with the PPCT-1 technique was 149.44 ± 2.84 µm, while with the PPCT-2 technique, it was 159.51 ± 2.72 µm (p
Keywords: Peripapillary choroidal thickness; OCT; Glaucoma